Microstructural and mechanical properties of submerged multi-pass friction stir processed AA6082/AA8011 TIG-welded joint. (2021) - Msomi, Velaphi; Mabuwa, Sipokazi; Merdji, Ali; Muribwathoho, Oritonda; Motshwanedi, Sharon S.
Abstract: This paper reports on the correlation between the microstructure and mechanical properties of the AA6082/AA8011 TIG-welded joint that was subjected to the submerged multi-pass friction stir processing (MFSP). The two dissimilar materials were joined through the TIG welding technique. The TIG-welded joints were then subjected to underwater (submerged) MFSP with water being kept at room temperature. The microstructural analysis showed that the increase in the number of FSP passes resulted in the refinement of grains. The increase in the number of FSP passes had a marginal impact on tensile strength but a major influence on percentage elongation. The increase in the number of FSP passes also resulted in an increase in microhardness of the stir zone.